Educational intervention on the cervical-uterine cancer prevention in women from the Las Flores doctor's office 7. Nuevitas - Magdiel Galiano Silva; Tania Sánchez Roja; Rebeca Rodríguez Mesa; Maira Pérez Basulto; Vilda Magalys Valdez Cervante; Yenly Loucratf Primelle (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: cervical-uterine cancer represents 10% of all cancer causes. Its prevention is essential and educating about it is fundamental. Objective: to describe the result of an educational intervention on cervical-uterine cancer in women from doctor's office 7, Nuevitas. Methods: intervention study that included 86 women from 18 to 55 years of age, from the X Anniversary Community Teaching Polyclinic, in Nuevitas, Camagüey. A survey was applied that allowed measuring the knowledge level before and after the educational intervention. The analyzed variables were age, educational level, knowledge about risk factors and suspicious manifestations, and about the cytological test. Results: there was a predominance of women with completed primary level and those under 44 years of age. At the beginning of the study, they showed low knowledge about risk factors, especially the beginning of early sexual relations (54.6%) and infections by papilloma virus, HIV/AIDS and genital herpes (56.9%). 65.11% did not know that vaginal discharge is a suspicious manifestation, and 82.5% had insufficient knowledge about the cytological test. All these parameters increased above 80% and most of them 95% after the intervention, except knowledge about inadequate diet as a risk factor, which only rose to 70.9%. Conclusions: a notable increase in knowledge about risk factors, suspicious manifestations and the importance of the cytological test was achieved, which implies a benefit in the prevention of cervical-uterine cancer.